BRAND ARCHITECTURE RECOMMENDATIONS FOR TINKER GAMES BRAND ALIGNMENT WITH THE PARENT COMPANY - Muhammad Farizan, Nur
It is known that the video game industry is growing every year and generate $137.9 billion revenue in 2018 with 11% CAGR, and estimated will reach $180.1 billion in 2021. Even Indonesia is the 2 nd place in video game revenue reach $US 465.36 million in 2017 and it has a huge potential to become number one in Southeast Asia, especially in mobile games. In contrast with the increasing of the global video game industry revenue, Tinker Games, one of Indonesia mobile game developer, face a declining of their revenue. This declining occurred because of their lack of their marketing campaign and low of their brand awareness. Brand awareness is one aspect in the branding, while branding is one important element in video games marketing strategy. But recently, Tinker Games get a good news that is new investors who join the company and build a new entity that will become a parent company. But, that situation is also create a new problem that is the alignment of Tinker Games brand equity with the new goals of the parent company. The analysis of this part will using brand audit concept that consist of brand inventory and brand exploratory. Brand Inventory will analyze the current condition of all product or services sold, environment and marketing communication that are marketed and branded in the company perspective. While brand exploratory will analyze the consumer brand awareness level in the consumer perspective and current competitive condition. The factor that influence brand gaps and low brand awareness level of Tinker Games will be explained in the brand audit summary. At the end of the process, the author assumes that there are five root cause in this research, those are: the first is have no sub-brand alignment, the second is lack of marketing campaign, the third is poor of customer’s engagement, the fourth is low effectiveness of current marketing campaign, and the fifth is have no strong differentiation. After knowing the root cause of this issue, strategy designed for business solution using brand reinforcement strategy. Solution proposed including 1) build more potential marketing campaign, 2) evaluate current marketing campaign, 3) provide customers engagement forum, 4) create new strong unique differentiation, and 5) create new sub-brand alignment and architecture. Proposed solutions on this research will be implemented in the marketing mix. By implementing solution based on brand reinforcement strategy, hopefully that it will solve Tinker Games brand awareness and sub-brand alignment business issues.